Education and Economic Growth - Hu, Sheng Cheng (Review of Economic Studies, 1976)
Journal Article Education and Economic Growth Get access Sheng Cheng Hu Sheng Cheng Hu Purdue University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 3, October 1976, Pages 509–518, https://doi.org/10.2307/2297229 Published: 01 October 1976 Article history Received: 01 January 1974 Accepted: 01 December 1975 Published: 01 October 1976